Presence of pharmaceuticals in benthic fauna living in a small stream affected by effluent from a municipal sewage treatment plant. (1st April 2015) - Grabicova, Katerina; Grabic, Roman; Blaha, Martin; Kumar, Vimal; Cerveny, Daniel; Fedorova, Ganna; Randak, Tomas
Abstract: Aquatic organisms can be affected not only via polluted water but also via their food. In the present study, we examined bioaccumulation of seventy pharmaceuticals in two benthic organisms, Hydropsyche sp. and Erpobdella octoculata in a small stream affected by the effluent from a sewage treatment plant (STP) in Prachatice (South Bohemia region, Czech Republic). Furthermore, water samples from similar locations were analyzed for all seventy pharmaceuticals. In water samples from a control locality situated upstream of the STP, ten of the seventy pharmaceuticals were found with average total concentrations of 200 ng L −1 . In water samples collected at STP-affected sites (downstream the STP′s effluent), twenty-nine, twenty-seven and twenty-nine pharmaceuticals were determined at average total concentrations of 2000, 2100 and 1700 ng L −1, respectively. Six of the seventy pharmaceuticals (azithromycin, citalopram, clarithromycin, clotrimazole, sertraline, and verapamil) were found in Hydropsyche . Four pharmaceuticals (clotrimazole, diclofenac, sertraline, and valsartan) were detected in Erpobdella . Using evaluation criterion bioconcentration factor (BCF) is higher than 2000 we can assign azithromycin and sertraline as bioaccumulative pharmaceuticals. Even pharmaceuticals present at low levels in water were found in benthic organisms at relatively high concentrations (up to 85 ng g −1  w.w. for azithromycin). Consequently, the uptake of pharmaceuticals via the food web could be an important exposure pathway for the wild fish population. Graphical abstract: Highlights: Pharmaceuticals bioaccumulate in benthic fauna living downstream the effluent. Azithromycin, clarithromycin, verapamil and citalopram were found in Hydropsyche . Diclofenac and valsartan were determined in Erpobdella . Only sertraline and clotrimazole were found in both studied species. Uptake of pharmaceuticals via food web can be important exposure pathway for fish.